The Effect of Group Investigation Learning Model on Students' Critical Thinking Ability in Pancasila Education Courses - Disurya, Ramanata; Hamzah, Syukri (Graduate Program Magister Manajemen Pendidikan, 2022)
The purpose of this study is to see how the group investigation learning model affects students' critical thinking skills in Pancasila education courses. A quasi-experimental approach with a nonequivalent control group was adopted for the investigation. The demographic utilized is all PGSD Study Program students. The control class has 35 pupils, whereas the experimental class has 33 people. The experimental class employs the group investigation learning model, whereas the control group employs a traditional learning model. In this study, the average pretest value of the experimental class is 35.4, whereas the control class's pretest value is 35.8. The average value of critical thinking abilities on the posttest differed between the two learning regimens. The group investigation learning approach has a substantial impact on the critical thinking abilities of PGRI University Palembang students enrolled in the Pancasila Education course.